Injectable Porous Microspheres: Metabolism Balance Regulation via Antagonist‐Functionalized Injectable Microsphere for Nucleus Pulposus Regeneration (Adv. Funct. Mater. 52/2020). (22nd December 2020) - Xu, Yichang; Gu, Yong; Cai, Feng; Xi, Kun; Xin, Tianwen; Tang, Jincheng; Wu, Liang; Wang, Zhen; Wang, Fei; Deng, Lianfu; Pereira, Catarina Leite; Sarmento, Bruno; et al.
Abstract : Inspired by the inflammation of the intervertebral disc degene ration microenvironment, in article number 2006333, Bruno Sarmento, Wenguo Cui, Liang Chen, and co‐workers design antagonist‐functionalized injectable porous microspheres with functions of modulating inflammation responses and regulating extracellular matrix metabolism balance to satisfy the specific demand on early‐stage restoration of the intervertebral disc microenvironment and its regeneration.